Mitochondrial DNA Pathogenic Variant Prevalence in Primary Mitochondrial Disease Patients With African (L) Mitochondrial Genome Haplogroups - Surita Meldau; Elizabeth M. McCormick; Ibrahim George‐Sankoh; Gillian T. Riordan; Kashief Khan; Laura E. MacMullen; Shrinav Dawlat; Dee Blackhurst; Marni J. Falk; Joanna L. Elson (JIMD Reports, 2025)
ABSTRACT Primary mitochondrial diseases (PMD) are caused by pathogenic variants in over 350 genes, 37 of which are located in mitochondrial DNA (mtDNA). While more than 100 mtDNA variants have confirmed disease associations, there are few reports of mtDNA‐related PMD in patients with African heritage, even in well‐studied populations. We investigated the frequency of pathogenic mtDNA variants in African L‐haplogroups in patients with confirmed PMD from two diagnostic cohorts. Data from genetically confirmed mtDNA‐related cases were extracted from existing databases at the National Health Laboratory Service Inherited Metabolic Disease Laboratory in South Africa (SA), and the Children's Hospital of Philadelphia (CHOP) Mitochondrial Medicine Frontier Program (USA). Mitochondrial genome haplogroup context was recorded from existing sequence report data. Stored DNA from the remaining cases was sequenced for mitochondrial genome haplogroup determination. Haplogroup context was obtained for 82 SA and 165 CHOP PMD cases. Sixty‐two (47 SA; 15 USA) PMD cases from at least 50 maternal lineages were found to carry L Haplogroups. Unique L sub‐haplogroups were identified in 11 (9 SA, 2 USA) families with the m.3243A>G MELAS variant, 6 SA families with the m.11778G>A LHON variant, and 20 (15 SA, 5 USA) cases with single large‐scale mtDNA deletions (4 of whom had the 4977 bp common deletion). Several additional well‐documented mtDNA pathogenic variants were identified in L‐haplogroup context. PMD patient clinical features correlated closely with those described in other haplogroup cohorts. This study demonstrates that common pathogenic mtDNA variants occur in the context of multiple African mtDNA lineages. Disproportionately low diagnostic rates highlight ongoing diagnostic inequalities affecting those on the African continent and African patients globally.